STRUCTURAL GEOLOGY FAULT EFFECT ON HIGHWALL COAL MINING AND FAILURE EVALUATION BASED ON VELOCITY DATA AT BENGALON, EAST-KUTAI DISTRIC, EAST KALIMANTAN PROVINCE. - Muh Arif Idhan; Gina Audina Alhabsyi; Muhammad Ikbal (Indonesian Mining Professionals Journal, 2021)
The geological structure especially folds and faults will reduce slope stability at slope mining where many events are the main factors that trigger slope failure. The geological structure "unknown" is defined as a minor geological structure that was not defined in the initial geological modeling. This uncertainty geological structure is critical issue during the mining process in coal mining. Slope stability Radar is a monitoring instrument that has been used in this research. In SSR data analysis, graphical behavior from velocity data is for monitoring program. The analysis in this research consisted of measuring the geological structure in the area where slope failure occurred and reading the velocity acceleration data from SSR instrument.Slope failure in this research study conduct on the high-wall coal mining which is in line with the geological structure plane with direction N 2460 E and dip 480, along + 150 m and at elevations RL +30 to RL -10. Velocity value at the time of slope failure was 13,568 mm/hour. This value can then be used as a reference as the “Progressive Velocity” value before the slope failure occurs at certain slope wall conditions.The content case study is expected to help engineers in increasing confidence in determining the characteristics of slope failure based on Velocity data in areas that have a geological structure, however, this study research aims to determine basic behavior in the SSR monitoring program and serve as a reference in the risk management program in the coal Mining industry.